Peran Pendidikan Tasawuf dalam Membentuk Karakter Religius Remaja Muslim - Munding Kurnianto; Andri Saepul Hamdi; Muhamad Budi Setiawan; Muhammad Rizky Fadhilah; Ismail Mubarok; M. Ridwan Saputra (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the role of Sufism education in shaping the religious character of Muslim adolescents in the midst of the challenges of the modern era characterized by moral degradation and spiritual crisis. The approach used in this study is a qualitative method with the type of library research, through the analysis of various relevant literature on Sufism and character education. The results of the study show that Sufism education has a significant contribution to the formation of religious character through the internalization of spiritual values such as sincerity, patience, tawakal, and self-control. These values are able to form a balance between intellectual, emotional, and spiritual aspects in adolescents. In addition, the integration of Sufism in Islamic education can be an effective solution in overcoming moral crises, negative environmental influences, and challenges of technological developments that affect adolescent behavior. Sufism education is not only oriented to the cognitive aspect, but also to the development of the soul (tazkiyatun nafs) which has an impact on real behavioral changes in daily life. Thus, Sufism education plays an important role in creating a generation of Muslims who have noble character, have high spiritual awareness, and are able to deal wisely with the dynamics of modern life.